2012
DOI: 10.1111/j.1460-9568.2012.08000.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the central nucleus of the amygdala reduces the effect of punishment on cocaine self‐administration in rats

Abstract: Continued cocaine use despite the negative consequences is a hallmark of cocaine addiction. One such consequence is punishment that is often used by society to curb cocaine use. Unfortunately, we know little about the mechanism involved in regulation by punishment of cocaine use. The fact that cocaine addicts continue cocaine use despite potential severe punishment suggests that the mechanism may be impaired. Such impairment is expected to critically contribute to compulsive cocaine use. This study aimed to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 58 publications
(112 reference statements)
4
33
0
Order By: Relevance
“…Also, only ~50% of rats exhibit footshock-resistant alcohol intake when 1 in 8 FR3 responses is paired with footshock (Seif et al, 2013), while all rats reduce responding when 1 in 3 FR3 responses are paired with footshock (S. J. Chung and F. W. Hopf, unpublished). This is similar to what is observed with footshock-resistant cocaine intake, where enough shocks c reduce responding in all rats (Xue, Steketee, & Sun, 2012), and even completely eliminate responding (i.e., a self-induced abstinence; Barnea-Ygael et al, 2012; Cooper, Barnea-Ygael, Levy, Shaham, & Zangen, 2007). In addition, after short-term intake, all rats show reduced cocaine intake by Pavlovian-conditioned aversive stimuli, while after long-term intake all rats are resistant to suppression of intake by these cues (Vanderschuren & Everitt, 2004).…”
Section: Are There Subpopulations Of Compulsive Rats?supporting
confidence: 83%
See 1 more Smart Citation
“…Also, only ~50% of rats exhibit footshock-resistant alcohol intake when 1 in 8 FR3 responses is paired with footshock (Seif et al, 2013), while all rats reduce responding when 1 in 3 FR3 responses are paired with footshock (S. J. Chung and F. W. Hopf, unpublished). This is similar to what is observed with footshock-resistant cocaine intake, where enough shocks c reduce responding in all rats (Xue, Steketee, & Sun, 2012), and even completely eliminate responding (i.e., a self-induced abstinence; Barnea-Ygael et al, 2012; Cooper, Barnea-Ygael, Levy, Shaham, & Zangen, 2007). In addition, after short-term intake, all rats show reduced cocaine intake by Pavlovian-conditioned aversive stimuli, while after long-term intake all rats are resistant to suppression of intake by these cues (Vanderschuren & Everitt, 2004).…”
Section: Are There Subpopulations Of Compulsive Rats?supporting
confidence: 83%
“…A second possible explanation for CeA control over compulsive drug use may lie in the well-described CeA control of sensitivity to negative emotional stimuli and punishment (Ciocchi et al, 2010; Maren & Quirk, 2004; Phelps & LeDoux, 2005; Sehlmeyer et al, 2009). Indeed, CeA lesions reduce conditioned suppression, i.e., the suppression of ongoing operant behavior by a conditioned fear stimulus (Killcross, Robbins, & Everitt, 1997), and reduce direct suppression of behavior by footshocks (Xue et al, 2012). Taken together, there is ample reason to suggest the importance of the amygdala in both escalation of alcohol intake and the development of compulsive drug use.…”
Section: Molecular and Circuit Mechanisms That Promote Aversion-resismentioning
confidence: 99%
“…With regard to the resistance to punishment discussed here, it has been shown that lesions of the CeA reduced conditioned suppression, i.e., the suppression of ongoing operant behavior by a conditioned fear stimulus (Killcross et al, 1997). A recent study extended these findings and showed that the CeA also contributes to the sensitivity to punishmentinduced suppression of cocaine self-administration (Xue et al, 2012). Taken together, there is substantial literature demonstrating the involvement of the amygdala in both the escalation of drug use and the development of compulsive drug use.…”
Section: Amygdalasupporting
confidence: 52%
“…In humans, the reduction of amygdala volume has been related to increase in desire for alcohol and cocaine intake and greater tendency to relapse [56], while in rats its functional block leads to increase in compulsivity of cocaine intake and seeking and reduction of its anxiety-producing effect [57,58]. However, DBS of the amygdala does not find a clinical application in the treatment of addiction at present, even if it has been proposed by some authors [59].…”
Section: Amygdalamentioning
confidence: 99%